Preoperatif Değerlendirme Uzlaşı Raporu Özeti (ÇEŞİTLİ ) - Ozkan, Metin; Kırkıl, Gamze; Dilektaşlı, Aslı Görek; Söğüt, Ayhan; Sertogullarindan, Bunyamin; Çetınkaya, Erdogan; Kovan, Tezay (My University, 2015)
-
Keywords: Cerrahi